Commentary on “Why am I still in hospital? Evaluation of delayed discharges from two learning disability assessment and treatment units in England” - Shankar, Rohit (Tizard learning disability review, 2023)
Purpose This commentary explores the challenges and themes enumerated by the associated article “Why am I still in hospital? Evaluation of delayed discharges from two learning disability assessment and treatment units in England”. This commentary broadens and outlines the research’s background, premise and potential impact. This paper aims to critically examine the evidence on this subject. Design/methodology/approach This commentary considers the attitudes to inpatient care for people with learning disabilities in the past decade and outlines a possible compact for the future. Findings Contrary to popular and emotive beliefs that using specialist inpatient psychiatric settings for people with learning disabilities is universally a poor practice, there are defined occasions when such settings are needed and imperative in the clinical pathway. If people with learning disabilities can access inpatient settings at the right time for the right reason, psychiatric outcomes could be improved. Timely discharge is imperative and currently lacking due to a lack of suitable engagement mechanisms between inpatient settings and the community. Thus, evidence-based outcome tools are essential to facilitate appropriate discharge. Originality/value There is an ongoing debate on the value and utility of specialist inpatient psychiatric units for people with learning disabilities. This commentary provides a balanced, evidence-based insight into this discussion.